Design and Dynamic Performance Study on Hydrostatic Lubrication System of High-speed Precision Roller Grinding Head - Huai-chao, Wu; Li-mei, Zhao; Wen-meng, Yan; Lei, Xu (Manufacturing Technology Journal, 2019)
To meet the need of high-speed steel roll grinding, a hydrostatic lubrication system for high-speed precision roller grinding head is designed and the dynamic performance of the system is simulated and analyzed in this study. The hydrostatic lubrication system was designed according to the lubrication characteristics of the eccentric sleeve and thrust bearing of the high-speed precision roller. Then the mathematical models of the main components of the system were established. And according to the schematic diagram of hydrostatic lubrication system, the dynamic performance of the lubrication system at high speed was simulated and tested. The simulation and experiment results show that the lubrication effect of the eccentric sleeve static chambers and thrust bearings is good, and the designed hydrostatic lubrication system is feasible.
Keywords: High-speed precision roller grinding head; AMESim; Lubrication system; Dynamic performance